EXTRACTION, IDENTIFICATION AND QUANTIFICATION OF RED CLOVER ISOFLAVONES USING NATURAL DEEP EUTECTIC SOLVENTS BY HPLC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents the geographical location of vegetation and the characteristics of the vegetative growth of red clover. Chemical composition of red clover, presence of isoflavones in flowers. Data on the current information on the biological and pharmacological effects of flavonoids isolated from red clover are presented.
Keywords: plant material, phytoestrogens, isoflavonoids, extraction methods, extract of red clover flowers